2012
DOI: 10.1111/j.1467-9655.2011.01733.x
|View full text |Cite
|
Sign up to set email alerts
|

The pastor and the prophetess: an analysis of gender and Christianity in Vanuatu

Abstract: The focus of this article is the proliferation of new charismatic Pentecostal churches in the South Pacific nation Vanuatu. The established Presbyterian Church on the island of Ambrym is compared to a new Pentecostal church in the capital Port Vila in terms of gender. The idea of a vanishing form of masculinity and the development of a form of ‘gender nostalgia’ is emphasized in the comparison. By looking at gender relations, new perspectives on the difference between the new churches and more established chur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…With such a perspective it is possible to establish a connection between the reformulation of gendered values and the overall framework of a conversion project intended to realise a novel form of Pentecostal masculinity. In this chapter, part of this analytical connection was developed by looking into to what Annelin Eriksen has termed the ‘sociological dimension of Pentecostal Christianity and its effect on men and women’ (Eriksen : 110). This analysis highlighted how gendered roles, religious laws, church structures and domestic arrangements puzzle together in cogent ways.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With such a perspective it is possible to establish a connection between the reformulation of gendered values and the overall framework of a conversion project intended to realise a novel form of Pentecostal masculinity. In this chapter, part of this analytical connection was developed by looking into to what Annelin Eriksen has termed the ‘sociological dimension of Pentecostal Christianity and its effect on men and women’ (Eriksen : 110). This analysis highlighted how gendered roles, religious laws, church structures and domestic arrangements puzzle together in cogent ways.…”
Section: Resultsmentioning
confidence: 99%
“…In Melanesia, Annelin Eriksen pioneered the study of Pentecostalism from a gender perspective (Eriksen ). She observed that, in order to study the then novel burgeoning of Pentecostal Churches in Vanuatu, an understanding of Pentecostal values as gendered values would ‘illuminate the difference between the new churches and more established churches’ (Eriksen : 103). Building upon the basis of this observation, she was able to illustrate how the new churches create a space in which Pentecostal Christians work out a novel form of masculinity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barker questions this dualistic approach to Christianity, noting that in much of the Pacific, Christianity is part of a ‘neo‐traditional complex’ and is not experienced as a rupture with the traditional past (2012: 68). Others also question an exclusive focus on individualism in defining Christianity, and emphasise the collective work of congregations and fellowships over individuals’ choices (McDougall , ; Van Heekeren ; Weichart ; Eriksen ). Several find that Christianity is often conflated with ethnicity and nationhood (Armstrong ; Kaplan ; Eriksen ; Dundon ).…”
Section: Christianity and Anthropology In The Pacificmentioning
confidence: 99%
“…Strathern's ‘The Gender of the Gift’ () is perhaps the primary example, with the works of many others such as Annette Weiner (), Lisette Josephides (), and Margaret Jolly (; Jolly and Macintyre ), among others, also using gender and/or feminist frameworks as an analytical tool for understanding the material realities, social relations and organisation, and cosmologies of Melanesian societies. There is, however, very little attention in the anthropological literature on bringing these two areas of research together (however, see Eriksen , , ; Jolly ). This collection is an effort at doing exactly this…”
Section: Introductionmentioning
confidence: 99%